Context-dependent dysregulation of store-operated calcium channels in head and neck squamous cell carcinoma - Heba Ghozlan; Saja Al-Malahmeh; Othman Al-Shboul; Anas J. Mistareehi; Lina Elsalem (PLoS ONE, 2026)
Store-operated calcium entry (SOCE), mediated by ORAI1–3 calcium channels and stromal interaction molecules STIM1 and STIM2, is increasingly recognized as a regulator of cancer progression. However, its role in head and neck squamous cell carcinoma (HNSCC) and its relationship with major oncogenic pathways remain poorly defined. Transcriptomic and clinical data from The Cancer Genome Atlas (TCGA) were analyzed to profile isoform-specific ORAI1–3 and STIM1–2 expression across HNSCC subtypes and oncogenic contexts. In parallel, the effects of pharmacologic SOCE inhibition with 2-aminoethoxydiphenyl borate (2-APB) were evaluated in FaDu (epidermal growth factor receptor [EGFR]-high, PIK3CA–wild-type) and Detroit-562 (metastatic, PIK3CA–mutant) cells by assessing viability, migration, and clonogenic survival. TCGA analysis revealed a context-dependent SOCE expression profile. ORAI1–3 and STIM2 were broadly upregulated in tumors, while STIM1 was significantly downregulated, particularly in advanced and basaloid subtypes. PIK3CA mutations, especially the H1047R hotspot, were associated with higher STIM1 expression, whereas EGFR expression correlated positively with STIM1/2 but negatively with ORAI1/3. In vitro, Detroit-562 cells expressed higher levels of SOCE components and showed greater sensitivity to SOCE inhibition, with marked reductions in viability, migration, and clonogenic capacity. FaDu cells, despite higher EGFR expression, exhibited lower SOCE gene expression and relative resistance to 2-APB, which suggests reduced dependence on SOCE-mediated signaling. These findings suggest that SOCE components are transcriptionally dysregulated in HNSCC and may represent a context-dependent therapeutic vulnerability, particularly in PIK3CA-mutant tumors. Validation in additional preclinical models, patient-derived xenografts, and clinical specimens is required to establish SOCE as a biomarker and therapeutic target in HNSCC.